The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1093/jac/19.5.671
|View full text |Cite
|
Sign up to set email alerts
|

Biliary elimination of ceftazidime

Abstract: When five normal subjects were given ceftazidime 2 g iv, antibiotic concentrations in aspirated duodenal fluid increased progressively during 4 h to a value of 21.2 +/- 9.2 mg/l (mean +/- S.E.M.); 0.05% of the dose given was recovered in duodenal fluid. The same dose was given to 12 patients with an external biliary drain. The mean peak ceftazidime concentration of 36.3 +/- 4.0 mg/l was reached in the collected bile during the second hour after administration. The 12-h biliary recovery was 0.21% of the dose. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Comparison ofELF, lymph, blood, and urine rAAT levels demonstrated that the process was concentration dependent, with highest levels in ELF and in descending concentrations with 410-fold concentration differences in each consecutive compartment, respectively. Importantly (6,7), and studies with recombinant interferon-'y, interferon-a, and granulocytemonocyte colony-stimulating factor, erythropoietin, and interleukin 2 have necessitated subcutaneous, intramuscular, or intravenous routes of administration (1-5, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparison ofELF, lymph, blood, and urine rAAT levels demonstrated that the process was concentration dependent, with highest levels in ELF and in descending concentrations with 410-fold concentration differences in each consecutive compartment, respectively. Importantly (6,7), and studies with recombinant interferon-'y, interferon-a, and granulocytemonocyte colony-stimulating factor, erythropoietin, and interleukin 2 have necessitated subcutaneous, intramuscular, or intravenous routes of administration (1-5, 9, 10).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison ofELF, lymph, blood, and urine rAAT levels demonstrated that the process was concentration dependent, with highest levels in ELF and in descending concentrations with 410-fold concentration differences in each consecutive compartment, respectively. Importantly (6,7), and studies with recombinant interferon-'y, interferon-a, and granulocytemonocyte colony-stimulating factor, erythropoietin, and interleukin 2 have necessitated subcutaneous, intramuscular, or intravenous routes of administration (1-5, 9, 10).As an alternative approach to administration ofrecombinant proteins (and proteins in general, independent of the source), the present study was designed to capitalize on the enormous surface area of the lung as a potential absorptive surface through which proteins of therapeutic importance could gain access to the interstitium of the lung and plasma while remaining intact. This concept is based on the knowledge that (i) droplets of 3-,um diameter inhaled as an aerosol have the potential to reach the alveolar surface (11-14); (ii) the epithelial surface of the human lower respiratory tract is very large, typically 140 m2 in adults (15); (iii) plasma proteins as large as 100 kDa are found in the epithelial lining fluid surface of the lung, suggesting that proteins can diffuse across the capillary endothelium, the alveolar interstitium, and the alveolar epithelium (16)(17)(18)(19); and (iv) although there are no quantitative data available relating to the measurement of autologous natural or recombinant proteins from lower respiratory tract epithelial lining fluid to plasma, it is known that when solutions of heterologous proteins are instilled in the trachea of experimental animals, the protein can be subsequently detected in the pulmonary interstitium and blood (20)(21)(22).…”
mentioning
confidence: 99%
See 3 more Smart Citations